2007
DOI: 10.1016/j.metabol.2007.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduced meal frequency without caloric restriction on glucose regulation in healthy, normal-weight middle-aged men and women

Abstract: An unresolved issue in the field of diet and health is if and how changes in meal frequency affect energy metabolism in humans. We therefore evaluated the influence of reduced meal frequency without a reduction in energy intake on glucose metabolism in normal weight healthy male and female subjects. The study was a randomized cross-over design, with 2 eight-week treatment periods (with an intervening 11 week off-diet period) in which subjects consumed all of their calories for weight maintenance distributed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
210
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(224 citation statements)
references
References 38 publications
6
210
1
7
Order By: Relevance
“…This study shows that limiting energy intake to late in the day is detrimental for metabolic health in humans, although no differences in insulinemia were noted [49]. It is unclear whether limiting the calorie allowance to the morning, or at lunch would have impacted this outcome.…”
Section: Subjects (N)mentioning
confidence: 72%
See 2 more Smart Citations
“…This study shows that limiting energy intake to late in the day is detrimental for metabolic health in humans, although no differences in insulinemia were noted [49]. It is unclear whether limiting the calorie allowance to the morning, or at lunch would have impacted this outcome.…”
Section: Subjects (N)mentioning
confidence: 72%
“…Despite a small amount of weight loss, fasting blood glucose levels were increased, and TRF resulted in poorer glucose tolerance in response to an oral glucose tolerance test (OGTT) [49]. This study shows that limiting energy intake to late in the day is detrimental for metabolic health in humans, although no differences in insulinemia were noted [49].…”
Section: Subjects (N)mentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, far, relatively few RCTs of IER and TRF have been performed in human subjects, with the results of several studies of alternate-day and twice weekly energy restriction demonstrating weight loss and abdominal fat reduction and suggesting improvements in indicators of energy and lipid metabolism and inflammation (44-46, 51, 61). On the other hand, a study of TRF in which healthy normal weight subjects consumed a balanced daily food intake within a 4-h or 12-h time period each day revealed no improvement (79,80), which is similar to the lack of any short-term benefit of TRF in mice when the animals are fed a balanced diet (23). This finding suggests that the short-term benefits of TRF might depend on the diet and body composition.…”
Section: Future Directionsmentioning
confidence: 98%
“…No biomarkers were assessed. Another crossover study reported a 4.1% weight loss effect of consuming a single meal in the afternoon each day for 8 weeks without calorie restriction compared with an isocaloric diet consumed as three meals per day (15,99). The one meal per day condition was also associated with reductions in fasting glucose and improvements in LDL and HDL cholesterol.…”
Section: Time-restricted Feedingmentioning
confidence: 99%